Green manuring with crimson clover as an alternative to mineral fertilization in maize production one season results from northeast Croatia - Ambrušec, Ljubica; Gantner, Ranko; Herman, Goran; Gantner, Vesna; Bošnjak, Krešimir; Bukvić, Gordana (2021)
Role of mineral fertilizers is to complement the soils" indigenous supply of minerals for crop plants nutrition. Among the mineral nutrients, nitrogen is generally considered as the most yield-contributing. Obtaining nitrogen from legumes is potentially more sustainable than from industrial sources. Crimson clover (Trifolium incarnatum L.) has long been appreciated as cover crop grown for green manuring due to its capability for binding the atmospheric nitrogen into plant-available form. Green manuring effects of crimson clover for succeeding maize crop were tested in 2019 year on two locations of Northeastern Croatia differing in soil texture: 1) on the site A where the soil was compact and dominated by clay and 2) on the site B where the soil was loose and dominated by loam. The research was conducted in a year with favourable rainfall during maize vegetation. Results have shown that green manuring with crimson clover for maize as the main crop delivered somewhat lower maize grain and aboveground mass yields than the conventional full-dose mineral fertilization on deep fertile soils around Osijek (Northeastern Croatia). When compared to conventional agronomy, green manuring was associated with additional agrotechnical operations required for crimson clover cover crop establishment and its herbage incorporation into soil prior to seeding main maize crop. Research should be continued in more different environments (year × location combinations) in order to produce reliable evaluation of crimson clover"s green manuring services.
Bibliografija: 17 jed.
Abstract.
Keywords: Zelena gnojidba -- Grimizna djetelina -- Trifolium incarnatum L. -- Kukuruz -- Prinos